Virtual Reality “exergames”: A promising countermeasure to improve motivation and restorative effects during long duration spaceflight missions - Keller, Nathan; Whittle, Richard S.; McHenry, Neil; Johnston, Adam; Duncan, Colton; Ploutz-Snyder, Lori; Torre, Gabriel G. De La; Sheffield-Moore, Melinda; Chamitoff, Gregory; Diaz-Artiles, Ana (Frontiers in Physiology, 2022)
Long duration spaceflight missions will require novel exercise systems to protect astronaut crew from the detrimental effects of microgravity exposure. The SPRINT protocol is a novel and promising exercise prescription that combines aerobic and resistive training using a flywheel device, and it was successfully employed in a 70-day bed-rest study as well as onboard the International Space Station. Our team created a VR simulation to further augment the SPRINT protocol when using a flywheel ergometer training device (the Multi-Mode Exercise Device or M-MED). The simulation aspired to maximal realism in a virtual river setting while providing real-time biometric feedback on heart rate performance to subjects. In this pilot study, five healthy, male, physically-active subjects aged 35 ± 9.0 years old underwent two weeks of SPRINT protocol, either with or without the VR simulation. After a one-month washout period, subjects returned for a subsequent two weeks in the opposite VR condition. We measured physiological and cognitive variables of stress, performance, and well-being. While physiological effects did not suggest much difference with the VR condition over two weeks, metrics of motivation, affect, and mood restoration showed detectable differences, or trended toward more positive outcomes than exercise without VR. These results provide evidence that a well-designed VR “exergaming” simulation with biometric feedback could be a beneficial addition to exercise prescriptions, especially if users are exposed to isolation and confinement.